Predictors of procedural success and improvement of left ventricular ejection fraction after successful recanalization of coronary chronic total occlusion (CTO) - Ahmed Magdy; Khaled Shokry; Hany Foad; Wael Elkilany (Egyptian Journal of Chest Disease and Tuberculosis, 2017)
Objectives: This study sought to examine the pre-interventional parameters for procedural success of CTO angioplasty and to assess improvement of Left ventricular ejection fraction after successful angioplasty of CTO. Background: Chronic total occlusions (CTOs) are the most technically challenging lesion subset that interventional cardiologists might face, and that recanalization of these lesions will have the most impact on future percutaneous coronary interventions (PCI) success. Considering the recent development of catheter based technologies specific for CTO recanalization and the potential of drug-eluting stents, these lesions are now recognized as the last barrier to percutaneous revascularization success. Methods: 30 patients with CTO lesion(s) and evidence of viable myocardium underwent PCI in Kobry Elkobba hospital. We studied the effect of demographic data, angiographic data as lesion length, stump and proximal cap, calcification, angulation, bridging collaterals and distal cap and finally echocardiography pre and 3 months post procedural. Results: Procedural success was obtained in 25 patients (83.3%), 19 of them was antegrade and 6 was retrograde. There was no significant effect of different demographic data on the outcome, but angiographic criteria favoring success was tapered proximal cap, short lesions <15 mm, lesion angle <45 degree and no origin of side branch at the CTO segment. Stiff wires had the greatest chance to cross the CTO lesions, with the help of microcatheter. Rotablator was used to overcome heavily calcified plaques; IVUS was used to study the effect of plaque composition on the success of the procedure. There was significant reduction in LVIDd & LVIDs and highly significant increase in LVEF after successful recanalization of CTO. Conclusion: PCI for CTO lesions has achieved a better chance for success especially with modern facilities, but we should revise criteria of success and failure as this success has a considerable effect on LV function and patient outcome.